1990
DOI: 10.1136/bjo.74.5.305
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler imaging in the demonstration of an orbital varix.

Abstract: Depending on the direction of flow with respect to the transducer, the flow is displayed in either red or blue. The colours can be arbitrarily assigned, but by convention, and in this study, flow towards the transducer is depicted as red and away from the transducer as blue. When the eye and orbit are examined through the eyelids, the ultrasound beam is almost parallel to the orbital and ocular vessels; thus most arterial flow is depicted in red. Arteries can usually be distinguished from veins by noting the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…Neben Perfusionsstudien bei Glaukom findet die Doppler-Sonographie in der Augenheilkunde Anwendung bei der Darstellung von intraokularen Tumoren [10,17], Carotis-sinus-cavernosusFisteln [7], orbitalen Varizen [18] und okularen Gefäßverschlüs-sen [19].…”
Section: Introductionunclassified
“…Neben Perfusionsstudien bei Glaukom findet die Doppler-Sonographie in der Augenheilkunde Anwendung bei der Darstellung von intraokularen Tumoren [10,17], Carotis-sinus-cavernosusFisteln [7], orbitalen Varizen [18] und okularen Gefäßverschlüs-sen [19].…”
Section: Introductionunclassified
“…Diagnosis of many orbital diseases such as retinal and choroidal detachment, orbital varices, arteriovenous malformations, and vessel thrombosis is facilitated by detection of color flow within the investigated tissue. [1][2][3][4][5][6] In this report, we describe an artifact related to color Doppler flow imaging of the orbit. The color flow might be mistakenly interpreted as real blood flow if an examiner is not familiar with the artifact.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The blood flow is shown with this technique as a color map superimposed on a gray scale image of the examined structures. Diagnosis of many orbital diseases such as retinal and choroidal detachment, orbital varices, arteriovenous malformations, and vessel thrombosis is facilitated by detection of color flow within the investigated tissue.…”
mentioning
confidence: 99%
“…Different radiological methods can be used in the diagnosis of the orbital varix (Lieb et al 1990;Wildenhaim et al 1991). Magnetic resonance, the first performed radiological study in our patient, demonstrated bilateral retrobulbar masses.…”
Section: Discussionmentioning
confidence: 99%